Hubungan Antara Stres Kerja, Burnout dengan Resiliensi Perawat dalam Memberikan Asuhan Keperawatan di Ruangan Rawat Inap Rumah Sakit Umum di Kota Medan - Ummi Kalsum Sundari Ritonga; Jenny Marlindawani Purba; Wardiyah Daulay (Universitas Pahlawan Tuanku Tambusai, 2026)
Nurses are healthcare professionals who play a vital role in delivering 24-hours nursing care. However, the high work pressure makes them vulnerable to work related stress and burnout, which can affect their level of resilience in providing nursing services. This study aimed to analyze the relationship between work-related stress and burnout and nurses resilience in providing nursing care in the inpatient ward of a general hospital in Medan. This study used a cross-sectional designwith quantitative analytic approach. A sample of 165 nurses was selected using purposive sampling from RSU Haji Medan and RSUD dr. Pirngadi Medan. Data were collected using the Expanded Nursing Stress Scale (ENSS), the Maslach Burnout Inventory (MBI), and the Connor-Davidson Resilience Scale (CD-RISC). Data analysis used the Chi-Square test for bivariate analysis. The results showed that most nurses experienced varying levels of work stress and burnout, ranging from low to high.There is a significant association between work stress and resilience (p = 0.001) and between burnout and resilience (p = 0.001). In conclusion, work-related stress and burnout are significantly associated with nurses’ resilience. Hospital managerial interventions, such as stress coping training, psychological support, and resilience-building programs, are needed to maintain the quality of nursing care.